DAMPAK BENCANA BANJIR TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI KECAMATAN BATU BENAWA KABUPATEN HULU SUNGAI TENGAH, KALIMANTAN SELATAN - Reni Yunida; Rosalina Kumalawati; Deasy Arisanty (Universitas Lambung Mangkurat, 2017)
This study aims to determine : 1) The impact of floods on the social conditions of people in the District Batu Benawa, 2) The impact of floods on the economic conditions of people in the District Batu Benawa. This research is quantitative descriptive. The study population is families (KK) flood victims in Batu subdistrict Benawa totaling 364 respondents. The sampling technique using Proportional Sampling. Data collection techniques used were observation, interviews and documentation. The results showed that (1) The impact of floods on social respondents visible from : a) demographic conditions have not changed, there were no fatalities due to floods, b) health condition respondent, c) the state of education of household members (ART) of respondents experiencing barriers to learning d) of respondents experienced housing conditions change, which suffered damage to homes mild or only a small portion of damaged such as floor or wall of the house.(2) The impact of the floods on economic conditions seen from :a) conditions of livelihood respondents b) the condition of respondents' income changes, the number of respondents with a total income of low category. c) the ownership of valuables respondents judging from the number of respondents who have a motorcycle, television or radio or tape, and mobile phones, respondents who have a status of its own wetland damage.Keywords: Impact, cold lava flood, socio-economic condition